Shame on Me! Self-Conscious Emotions and Big Five Personality Traits and Their Relations to Anxiety Disorders Symptoms in Young, Non-Clinical Adolescents - Muris, Peter (Child Psychiatry Hum Dev, 2017)
This study explored the relations between self-conscious emotions, personality traits, and anxiety disorders symptoms in non-clinical youths. One-hundred-and-eighteen adolescents aged 12–15 years completed the brief shame and guilt questionnaire for children (BSGQ-C) and items of the youth self-report (YSR) to measure shame and guilt, the big five personality questionnaire for children, and the youth anxiety measure for DSM-5. Results for shame indicated that this self-conscious emotion—either measured by the BSGQ-C or the YSR—was uniquely and positively associated with a broad range of anxiety disorders symptoms, and correlated positively with neuroticism and negatively with extraversion. Guilt did not show significant associations with anxiety disorders symptoms once controlling for the influence of shame, and links with personality traits varied dependent on the assessment instrument that was used (BSGQ-C or YSR). Finally, when controlling for neuroticism and extraversion, shame consistently remained a significant correlate of anxiety disorders symptoms. Altogether, these results add to the growing body of evidence indicating that high levels of shame are clearly associated with anxiety pathology.